Effects of Aspect Ratio and Plate Thickness on the Behavior of Unstiffened Steel-Plate Shear Walls with Pinned and Rigid Connections - Rahim Abdi; Nader Abdoli Yazdi (Civil Engineering Journal, 2018)
Unstiffened steel plate shear walls (SPSWs) have been in use mostly in recent years. In this numerical study, the buckling behavior of a single-storey single-bay unstiffened SPSW with two pinned and rigid beam-column connections under lateral loading is investigated. The SPSW had different wall aspect ratios (L/h=1, 1.5, 2, 2.5, and 3) and infill plate thicknesses (tw= 3, 5, and 7 mm). Their effect on the buckling behavior of SPSW was examined using buckling analysis in ABAQUS software. Results indicated that with the increase of infill plate thickness, the lateral resistance of unstiffened SPSW system increases, but by increasing wall aspect ratio, its resistance decreases. In both connection designs, the model with L/h=1 (square-shaped model) showed better ductility and higher stiffness and strength in all three thicknesses. Maximum shear stress responses of SPSW models showed that in pinned design with L/h=1, the most change in shear stress values was 8% when infill plate thickness reached from 5 to 7 mm; while for rigid connection, it was reported as 7% when it increased from 3 to 5 mm. This indicates that in rigid connection, increasing the infill plate thickness has less effect on the increase of lateral resistance. By examining the performance of rigid and pinned beam-to-column connections with different wall aspect ratio and infill plate thickness, it was found out that maximum shear stress in rigid connection increased by 11% compared to pin connection. It was concluded that an optimum unstiffened SPSW model had a wall aspect ratio of 1 and infill plate thickness of 7 mm.